Physiological Response and Photosynthate Distribution of West Indian Arrowroot at Different Altitudes - Laksmi Puspitasari; Triadiati Triadiati; Sulistijorini Sulistijorini (AGRIVITA, Journal of Agricultural Science, 2019)
West Indian arrowroot (Maranta arundinacea L.) is a tuber crop that is consumed as an alternative food. İt can grow in an area with altitudinal range from 0 to 1,000 m asl. This study aimed to analyse physiological response and photosynthate distribution which is related to growth performance and tuber yield of West Indian arrowroot at two different altitudes. Four accessions of West Indian arrowroot i.e. Bantul, Krajan, Kemalang, and Begawat were planted at 250 and 1,100 m asl. This study was conducted using split plot design with altitude as the main plot and the accession of West Indian arrowroot as a subplot. The results showed that altitudes significantly affected physiological response, plant height, leaf area per plant, and tuber yield of West Indian arrowroot. The rate of photosynthesis in the highland tended to be higher than that in the lowland, but plant height and tuber yield were lower in highland. These results suggested that the West Indian arrowroot had different pattern on photosynthate distribution between shoot and tuber at different altitudes because of environmental factors. Bantul accession had the lowest tuber yield compared to the others, and showed the low ability of accession Bantul in distributing photosynthate towards tuber.